Halitosis in Children Undergoing Full Mouth Rehabilitation under General Anesthesia - Noura A. AlMadhi; Ayman M. Sulimany; Hamad A. Alzoman; Omar A. Bawazir (MDPI AG, 2021)
Interventions and management modalities of pediatric halitosis have been suggested in the literature, however, the effect of full mouth rehabilitation (FMR) under general anesthesia (GA) on pediatric halitosis was not reported. Therefore, the present study was conducted to investigate parents' perceptions of their child's halitosis before and after FMR under GA; and to evaluate the effect of FMR on clinical halitosis. Fifty-seven children between 3-8 years old, scheduled for FMR under GA, were included after satisfying the inclusion criteria and upon parental consent. Parents' perception of halitosis in their children was evaluated using a standardized questionnaire and a breath sample was collected to assess the level of volatile sulfur compounds (VSCs) using OralChromaTM before and after FMR under GA. Sixty percent (n = 34) of the parents perceived halitosis in their children before FMR and about 80% (n = 27) of them reported improvement in halitosis after FMR. Clinical halitosis was detected in 84.2% (n = 48) of the sample before treatment. A statistically significant reduction in halitosis was found in 56.3% (n = 27) of the children after treatment (p < 0.001). In conclusion, majority of parents perceived an absence or reduction of halitosis in their children following FMR and significant improvement of clinical halitosis.